Ezh2 Regulates Activation-Induced CD8+ T Cell Cycle Progression via Repressing Cdkn2a and Cdkn1c Expression - Chen, Guobing; Subedi, Kalpana; Chakraborty, Sayantan; Sharov, Alexie; Lu, Jian; Kim, Jaekwan; Mi, Xiaofan; Wersto, Robert; Sung, Myong-Hee; Weng, Nan-ping (Frontiers in Immunology, 2018)
Transition from resting to cell cycle in response to antigenic stimulation is an essential step for naïve CD8+ T cells to differentiate to effector and memory cells. Leaving the resting state requires dramatic changes of chromatin status in the key cell cycle inhibitors but the details of these concerted events are not fully elucidated. Here, we showed that Ezh2, an enzymatic component of polycomb repressive complex 2 (PRC2) catalyzing the trimethylation of lysine 27 on histone 3 (H3K27me3), regulates activation induced naïve CD8+ T cells proliferation and apoptosis. Upon deletion of Ezh2 during thymocyte development (Ezh2fl/flCD4Cre+ mice), naive CD8+ T cells displayed impaired proliferation and increased apoptosis in response to antigen stimulation. However, naive CD8+ T cells only had impaired proliferation but no increase in apoptosis when Ezh2 was deleted after activation (Ezh2fl/flGzmBCre+ mice), suggesting cell cycle and apoptosis are temporally separable events controlled by Ezh2. We then showed that deletion of Ezh2 resulted in the increase in expression of cyclin-dependent kinase inhibitors Cdkn2a (p16 and Arf) and Cdkn1c (p57) in activated naïve CD8+ T cells as the consequence of reduced levels of H3K27me3 at these two gene loci. Finally, with real time imaging, we observed prolonged cell division times of naïve CD8+ T cells in the absence of Ezh2 post in vitro stimulation. Together, these findings reveal that repression of Cdkn1c and Cdkn2a by Ezh2 plays an essential role in execution of activation-induced CD8+ T cell proliferation.